The Impact of Sister City Surabaya-Kitakyushu Cooperation on Environmental Development in Surabaya - Novia Millenia Nur Fitriana; Ba'adilla Nesya Nur Hakiki; Cahyo Wisnu Rubiyanto (Universitas Muhammadiyah Yogyakarta, 2022)
Surabaya is one of the largest cities in East Java and the Mayor of Surabaya has played an active role in improving infrastructure in recent years to realize a green city or better known as eco-city. This active role is motivated by the status of Surabaya which is classified as the region with the highest environmental pollution in East Java. The purpose of this study is to find out the environmental impact of the Surabaya Green City Plan implemented by the Surabaya City Government and Kitakyushu Shuangcheng. According to the authors of this study, it is interesting because participation in the sister city program between Surabaya and Kitakyushu has had a positive impact on Surabaya's environment. This research uses qualitative methods and gathers reliable sources as research references. To answer the research question, researchers usedgreen polyt ik theory and the concept of twin cities. The results of the study show that surabaya's city governance is now much better with green open space along its path, which makes Surabaya known as one of the best cities for waste management in Indonesia.